La contaminación por metales pesados en las Rías Baixas gallegas: nuevos valores de fondo para la Ría de Vigo (NO de España). - Rubio, B.; Vilas, Federico; Nombela, M.A. (Journal of Iberian Geology, 2000)
Pollution assessment in a given area depends mostly on the accurate determination of the so-called background values. Several authors have reported different background values for the Rías based on different statististical analyses but using only surface samples. New background values are proposed based on the metal concentrations determined by different techniques (atomic absorption spectrometry AAS- and X-ray fluorescence XRF-) for a long gravity core collected in a very highly polluted area in the Ría de Vigo. The validity of some previous background values is confirmed for Fe, Al, Mn, Ti, Ni, Co and Zn. New background values are proposed for Cu, Cr and Pb, 20, 55 and 25 µg g1, respectively. We revise the methods to minimize grain size effect, comparing the normalization with Al and Rb. In this sense, the diluting effect of the carbonates, masking the grain size effect, is emphasized. The contamination status for the Ría de Vigo is reinterpreted with the new background values. Moderate pollution for Cu, Zn and Cr was found. For Pb pollution was substantial in general terms, being very high in the bay of San Simón. The calculation of a metal pollution index allowed us to delimite the areas and pollution grades caused by these metals. The bay of San Simón and the surroundings of Vigo harbour were the most affected areas, showing the industrial influence.